NEW RECORD OF Theloderma annae Nguyen, Pham, Ngo, Nguyen, Ziegler, 2016 (ANURA: RHACOPHORIDAE) FROM NINH BINH PROVINCE, VIETNAM - Tuan Nam, Nguyen; Quang Vinh, Luu (Journal of Forestry Science and Technology, 2018)
We herein report a new provincial record of Theloderma annae Nguyen, Pham, Nguyen, Ngo, Ziegler, 2016 from Ninh Binh Province based on five collected specimens. Three of them were found in Trang An Landscape Complex and the remaining specimens were collected in Cuc Phuong National Park. Most specimens were detected on limestone cliffs, rarely appeared on the leaves. Our specimens are specially identical with the original description of Theloderma annae from Ngoc Son - Ngo Luong Nature Reserve, Hoa Binh Province by the following characters: 1) A small size Theloderma species (SVL 27.2 - 29.9 mm in males, 32.2 - 36.7 mm in females); 2) head longer than wide; 3) vomerine teeth absent; 4) snout long (SNL/SVL 0.16 - 0.19); 5) spines on upper eyelid absent; 6) tibiotarsal projection absent; 7) dorsal skin very smooth; 8) dermal fringes on forearm and tarsus absent; 9) dorsal surface greyish green; and 10) throat and ventral surfaces of arms and thighs brown with white spots. Theloderma annae’s distribution range is expanded to lower 100 m a.s.l. Our research brought the species number of the genus Theloderma known from Trang An Landscape Complex to one and from Cuc Phuong National Park to four species.